The comparison between oil palm productivity in flat, undulating and hilly area in haranky estate in Lahad Datu-case study / Nurul Izfahanie Sultan - Sultan, Nurul Izfahanie (Faculty of Plantation and Agrotechnology, 2016)
This case study investigated the achievable yield and revenue of oil palm yield for three types of topography that are flat, undulating and hilly area. This study also included rainfall rate and the monthly palm oil price in Haranky I Estate and Haranky 2 Estate. The objective of this case study is aimed to evaluate the difference in yield in the three types of topography, to determine the difference in yield between two estates in different topography and to determine the difference in revenue between the two estates. There is a significant difference of the yield per hectare in the three types of topography. In Haranky 1 Estate show that yield from July 2012 to June 2015 have different productivity. Both estates have the highest mean productivity of yield at undulating area followed by hilly area and flats area for Haranky1 Estate. For Haranky 2 Estate, second place is flat area and followed by hilly area. This is because the management practices between two estates is different. Besides, there are significant difference between the yield of production and types of topography in undulating and hilly area where the P -Value is less than 0.05 (p < 0.05). Unfortunately, there is no significant difference in flat area because the PValue is 0.638 (p > 0.05). This may happened because of the management practices that applied in flat area is different from undulating and hilly area. The plantation operation runs smoothly in the flat area because of the state of the topography makes all the operation run systematically. In terms of revenue, there are significant differences between the yield and the revenue . This is because of the repeated changing market price of oil palm. The market price keeps changing on each month for this 36 months. In the other hand, the production yield also influenced the difference of revenue between the two estates. It is hoped that this yield level will be sustained over a long period of time. The need for increased investment in oil palm research and the improvement of oil palm management practices is emphasized.